Assessing the impact of rice price stabilization policies in Bangladesh: Results from a stochastic spatial equilibrium model - Minot, Nicholas; Hossain, Shahadat; Kabir, Razin; Dorosh, Paul A.; Rashid, Shahidur (International Food Policy Research Institute, 2024)
Rice plays a central role in the diet in Bangladesh and as a source of income for farmers. Although Bangladesh has largely liberalized international trade in rice, it maintains a public food distribution system to stablize prices, distributing an average of 2 million tons of rice per year at a cost of almost US$ 800 million per year. This study explores whether alternative policies could achieve similar stabilization at a lower cost. It uses a stochastic spatial-equilibrium model of rice markets to simulate monthly prices in eight regions of the country. Stochastic shocks are used to simulate fluctuations in regional production, replicating historical patterns at the region-season level, as well as inter-regional correlation in production shocks. It also simulates fluctuation in world rice prices, mimicking the mean, variance, and serial correlation of historical wholesale prices of rice in Delhi. Public procurement and distribution follow historic averages by month and region. Private storage is represented by a simplified version of rational expectations models, in which net storage is a non-linear function of availability in the previous month.